Application of fungal pretreatment to produce monosaccharide from algae Spirogyra peipingensis - Fatiha, Lisa Ainayal; Husain, Dirayah Rauf; Sulfahri, Sulfahri (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2025)
Spirogyra peipingensis is a species of green algae known to have a high carbohydrate content, making it a promising alternative raw material for biosugar production. This study aimed to determine the effects of inoculum size and pretreatment duration on biosugar yield. The research was conducted in three stages: pretreatment, hydrolysis, and fermentation. Pretreatment was carried out to release polysaccharides, hydrolysis was performed to convert cellulose and hemicellulose into simpler forms, and fermentation was conducted to transform disaccharides into monosaccharides. Monosaccharide measurement was performed using an ATC refractometer with a refractive index method to estimate the total sugar content. The results showed that the combination of a 7.5% inoculum size with a fermentation duration of 24 hours produced the most optimal monosaccharide yield, amounting to 0.28 g/g substrate. These findings emphasize that the regulation of inoculum and pretreatment parameters plays a crucial role in enhancing the efficiency of algal biomass conversion into biosugar. Overall, this study contributes to the development of bioconversion technologies based on local biological resources and highlights the potential of Spirogyra peipingensis as an environmentally friendly raw material candidate for future biosugar industries.